ANALISA PERBANDINGAN ALGORITMA PUNCTURED ELIAS CODE DAN TABOO CODE PADA KOMPRESI FILE DOKUMEN - Ritonga, Fitri Sarmaito; Sembiring, Abdul Sani; Hutabarat, Sumiaty Adelina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
File document compression is a crucial technique for data transmission to reduce file size without losing relevant information. Large file sizes require substantial storage space. Document files are generally larger compared to other text file formats. Due to the large size of docx files, data transmission can be time-consuming. Compression is a technique used to address this issue by reducing the size of data. This study utilizes the Punctured Elias Code and Taboo Code algorithms, each with its own strengths and weaknesses. After compressing with both algorithms, a comparison was performed. The final results indicate that the Taboo Code algorithm is the fastest and most effective for compressing document files, as a smaller total value indicates less effort required by the algorithm in the compression process.